The impact of smart tourism on improving business performance - Kraja, Ambra; Goga, Irini; Kapaj, Ana (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of smart tourism on improving business performance, highlighting the increasing role of digital transformation in reshaping the tourism industry. As advancements in information and communication technologies (ICT), big data, and social media accelerate, tourism businesses and destinations are adopting smart tourism strategies to enhance operational efficiency, visitor satisfaction, and competitiveness. Smart tourism integrates data-driven technologies—such as sensor networks, real-time analytics, and interactive platforms—into destination planning and service delivery. A comprehensive literature review was conducted to identify the predominant methodologies and conceptual frameworks within the domain of smart tourism. Special emphasis was placed on the role of smart destination strategy and the influence of digital tools on tourist experiences and post-visit behaviors. Findings reveal that smart tourism technologies contribute significantly to the creation of efficient, personalized, and engaging tourism services, ultimately strengthening both visitor loyalty and business performance. The study concludes that adopting smart tourism is a strategic imperative for destinations and tourism enterprises seeking sustainable growth in an increasingly connected environment. These insights offer valuable implications for tourism stakeholders aiming to utilize smart technologies and digital platforms to enhance performance and meet evolving tourist expectations.